The triangle conspiracy - Kent, David (New York : Pocket Star Books, 2006)
When a troubled government agent comes to Department Thirty for assistance after becoming involved with the political extremist daughter of a prominent U.S. senator, only to have the woman turn up dead, Faith Kelly and Department Thirty find themselves targeted by a sinister assassin and an illusive mastermind who will do anything to destroy them all.
National College of Business and Arts
Keywords: Conspiracy -- Fiction; Political fiction